SPHEROIDAL NATIVE SELENIUM AS AN INDICATOR OF THE OPERATION OF HYDROTHERMAL PROCESSES IN COMPLEX HYDROGENEOUS DEPOSITS - Vinokurov S.F.; Menshikov V.V.; Sininkiy L.A. (My University, 1990)
Analysis of the collective data suggest that the spheroidal or spherical form of native selenium is an indicator of the operation of hydrothermal processes in the formation of complex ores in hydrogenous uranium deposits. Moreover, this indicator represents a special trigger, which permits the logical inclusion in the discussion of a hole spectrum of additional factual evidence, and opens the possibility of examining afresh specific genetic aspects, the most complex and most theoretical of which is the sources of the ore components for the formation of complex hydrogenous deposits. From this point of view it seems logical and sound to presume a significant, or possibly even a necessary, role of earlier anomalous concentrations of uranium and associated elements as the source for the formation of complex industrial ores in ore-bearing horizons, which were formed in association with the growth of an aureole of hydrothermally altered rocks, most probably belonging to a metasomatic association of low-temperature argillized rocks. This proposal is based on a combination of the following evidence: the constant and significant distribution in complex hydrogenous deposits of epigenetic alteration of the ore-bearing rocks, of so-called reducing series (dolomitization, pyritization, bitumenization, kaolinization, silicification, and so forth); the undoubted hydrothermal character of these transformed rocks, both on the evidence of thermobarometric studies, and their composition and zoning, which most closely resembles the low-temperature metasomatic association of argillized rocks.